Dengue infections in Colombia: epidemiological trends of a hyperendemic country (2020)
Abstract:Dengue is a major public health problem in hyperendemic countries like Colombia,the understanding of the epidemiological trends is important for the development of efficientpublic health policies. We conducted a systematic review of the epidemiologic data on dengue inColombia from 1971 to 2020. A total of 375 relevant citations were identified, 36 of which fulfilled theinclusion criteria. The data of dengue and severe dengue cases, infection fatality rate, and serotypedistribution were used to understand and identify gaps in the epidemiological knowledge in Colombia.The epidemiology of dengue in this country was characterized by five main outbreaks in 1998, 2002,2010, 2013, and 2019 with high fatality rates in comparison with the average values reported in theAmericas. The case fatality rate of severe dengue exceeded 2% and all four serotypes co-circulatethroughout the country with some regional variations. Overall, the behavior of dengue in Colombia isinfluenced by multiple factors including seasonal temperature variation and socioeconomic conditions.Additionally, the most important barriers in the epidemiological surveillance of dengue may be dueto the insufficient notification rate in some regions and the low active search for the circulation ofdifferent serotypes.